Kadar Lemak dan Organoleptik Rendang Dengan Penggunaan Serat Krim sebagai Substitusi Santan (Jurnal Peternakan Lingkungan Tropis, 2023)
The study aims to determine the uses of fibercreme as a substitute for coconut milk with different concentrations on the analysis of fat content and organoleptic acceptability of rendang. The study used a completely randomized design with four treatments and five replications. The data obtained was analyzed using variance (ANOVA) to determine differences between treatments and further analyzed using Duncan's Multiple Range Test (DMRT). The study showed that the treatment of using fibercreme as a substitute for coconut milk with different concentrations in rendang had no significant effect on the color test for the brightness value of L*, had a significant effect on the redness of a*, and had no significant effect on the value of yellowness of b*. The results of the study showed that the organoleptic quality was significantly different (P
Keywords: Array; Array; Array; Array